Coupled System of Nonlinear HyperbolicEquations with Variable-Exponents: GlobalExistence and Stability - Bouhoufani , Oulia; Hamchi, Ilhem (Mediterr. J. Math, 2020)
In this paper, we consider a coupled system of two nonlinear hyperbolic equations with variable-exponents in the damping and source terms. Under suitable assumptions on the intial data and the variable exponents, we prove a global existence theorem, using the Stable-set method. Then, we establish a decay estimate of the solution energy, by Komornik’s integral approach.